S STRATEGI KELAS IBU HAMIL DALAM PEMERIKSAAN ANTENATAL CARE DI PUSKESMAS SIMPANG TIGA PEKANBARU - Nindya Kirana; Islah Wahyuni; Yunni Safitri; Violita Dianatha Putri; Siti Zakiah Zulfa; Husna Farianti Amran; Dany Ariyani (JURNAL ABDIMAS DOSMA (JAD), 2024)
Antenatal care (ANC) is preventive care which aims to prevent and reduce complications for pregnant women. Pregnant women ensure that it is very important to have an ANC examination for healthy mothers and babies. Mothers who do not receive antenatal care have a higher risk of maternal death, other pregnancy complications and stillbirth. A strategy is needed so that pregnant women regularly check their pregnancy every month. The aim of the Pregnancy Class was developed for mothers to gain knowledge regarding their pregnancy. The aim of this activity is to provide knowledge and examination of ANC. P4S method (pre-test, counseling and sharing, SGD (Small group discussion), post-test and examination). The results showed an increase in the knowledge of pregnant women after community service. 90% (9 people) of pregnant women had good knowledge after being given counseling about Antenatal Care. Pregnant Women Class as a strategy to increase knowledge and utilization of maternal health services for Pregnant Women. Effort to visit ANC regularly. It is recommended that midwives remain optimistic and committed by continuing to empower Pregnant Women's Classes routinely, regularly and with direction.